PENINGKATAN HASIL BELAJAR IPS TENTANG AKTIVITAS PEMANFAATAN SDA MELALUI PEMBELAJARAN KOOPERATIF TEKNIK SQ3R PADA SISWA KELAS V SDN GLAGAHARUM - Kurniawan, Satunggale; Afifi Rahman, Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The SQ3R learning model in principle stands for the steps of studying a text, which include: First, Survey, namely examining or researching or identifying the entire text. Second, Question, namely compiling a list of questions that are relevant to the text. Third, Read, namely reading the text actively to find answers to the questions that have been arranged. Fourth, Recite, namely memorizing every answer that has been found. Fifth, Review, namely reviewing all the answers to the questions arranged in the second and third steps, we conducted a class action research (CAR) with the following title: